Job ladder, human capital, and the cost of job loss - Richard Audoly; Federica De Pace; Giulio Fella (Institute for Fiscal Studies (IFS), 2022)
High-tenure workers who lose their jobs experience a large and prolonged fall in wages and earnings. The aim of this paper is to understand and quantify the forces behind this empirical regularity. We propose a structural model of the labor market with heterogeneous firms, on-the-job search and accumulation of specific and general human capital. Jobs are destroyed at an endogenous rate due to idiosyncratic productivity shocks and the skills of workers depreciate during periods of non-employment. The model is estimated on German Social Security data. By jointly matching moments related to workers' mobility and wages, the model can replicate the size and persistence of the losses in earnings and wages observed in the data. We find that the loss of a job with a more productive employer is the primary driver of the cumulative wage losses following displacement (about 50 percent), followed by the loss of firm-specific human capital (about 30 percent).
Keywords: 330; Termination; loss of earnings; qualification; human capital; job search; labor mobility; labor market theory; structural model; Germany; Kündigung; Verdienstausfall; Qualifikation; Humankapital; Arbeitsuche; Arbeitsmobilität; Arbeitsmarkttheorie; Strukturmodell; Deutschland